Językowa percepcja zapachu w kulturze polskiej (na materiale eksperymentu psycholingwistycznego) - Yodlovska, Alina (Slavia Occidentalis, 2024)
The article presents the results of an experiment carried out with Polish language users, namely the linguistic representation of an unpleasant smell in Polish linguistic culture, and the smells identified by the speakers in the bathroom and the bedroom a reflection of these concepts in Polish dictionaries. Psycholinguistic realities differ from the lexicographic representation, there is no reference to smell in the dictionaries which, in my opinion, may hinder recognition specific objects.